Információs rendszerek a dél-alföldi élelmiszeripari társas vállalkozásokban - Hampel, György; Nagy, Elemérné (Jelenkori Társadalmi és Gazdasági Folyamatok, 2008)
Enterprise managers need reliable and processed information to make good decisions. To process the huge amount of data, computer based information systems are required. The self-made or standard information systems can be classified in many different ways: by the level of integration, level and type of decision support etc. Although computerized information systems are considered to give competitive advantage, it is not always easy to prove the return of investment when introducing such systems. According to the research conducted at bigger food industry enterprises in Hungary’s Southern Great Plain region, the use of integrated information systems are widespread. On the other hand, there are a lot of enterprises, where some tasks are accomplished with different small systems that have no connection with each other. The systems are capable of analysing the current situation but are rarely used for forecasting.